2021
DOI: 10.1016/j.celrep.2021.109415
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 variant B.1.617 is resistant to bamlanivimab and evades antibodies induced by infection and vaccination

Abstract: The emergence of SARS-CoV-2 variants threatens efforts to contain the COVID-19 pandemic. The number of COVID-19 cases and deaths in India has risen steeply and a SARS-CoV-2 variant, B.1.617, is believed to be responsible for many of these cases. The spike protein of B.1.617 harbors two mutations in the receptor binding domain, which interacts with the ACE2 receptor and constitutes the main target of neutralizing antibodies. Therefore, we analyze whether B.1.617 is more adept in entering cells and/or evades ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
130
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(144 citation statements)
references
References 73 publications
12
130
0
2
Order By: Relevance
“…Our data indicated that B.1.617 variant Spike promotes virus infectivity through enhanced viral entry and membrane fusion, which may play an important role in increased transmissibility of this variant. These findings are highly consistent with previous studies 20 . L452R mutation in the RBD was reported to increase SARS-CoV-2 infectivity and fusogenicity 21 .…”
Section: Discussionsupporting
confidence: 94%
“…Our data indicated that B.1.617 variant Spike promotes virus infectivity through enhanced viral entry and membrane fusion, which may play an important role in increased transmissibility of this variant. These findings are highly consistent with previous studies 20 . L452R mutation in the RBD was reported to increase SARS-CoV-2 infectivity and fusogenicity 21 .…”
Section: Discussionsupporting
confidence: 94%
“…Neutralization titers were found to be lower in all relative to the WT; B.1.617.1 was 6.8 times less susceptible to neutralization by convalescent and vaccinee sera [ 49 ]. Another study evaluating the degree of inhibition of S protein–ACE 2 interaction and subsequent cell entry by convalescent sera from intensive care unit patients revealed a twofold reduction in inhibition relative to the WT; by comparison, the delta variant showed a sixfold decrease [ 50 ]. Additionally, delta showed a threefold reduction in inhibition by sera obtained from individuals who received the Pfizer-BioNTech vaccine compared to WT.…”
Section: Efficacy Of Vaccines Convalescent Sera and Neutralizing Antibodies On Sars-cov-2 Variantsmentioning
confidence: 99%
“…Additionally, delta showed a threefold reduction in inhibition by sera obtained from individuals who received the Pfizer-BioNTech vaccine compared to WT. In contrast, beta exhibited an elevenfold reduction [ 50 ]. Monotherapy with either mAb failed to inhibit virus-host cell interactions [ 43 , 50 ].…”
Section: Efficacy Of Vaccines Convalescent Sera and Neutralizing Antibodies On Sars-cov-2 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutralization of various spike variants was assessed with the help of spike-pseudotyped simian immunodeficiency virus particles as described before 85 . For the production of pseudotyped reporter particles, HEK293T cells were transfected with the SIV-based self-inactivating vector encoding luciferase (pGAE-LucW), the SIV-based packaging plasmid (pAdSIV3), and the respective spike variantencoding plasmid [86][87][88] . For this purpose, 2x10 7 HEK293T cells were seeded the day before in a 175 cm 2 flask in Dulbecco's Modified Eagle's Medium (DMEM; Gibco) containing 10% FCS, 2 mM L-Glutamine, and 100 units/ml penicillin/streptomycin (D10 medium).…”
Section: Pseudotype Neutralization Assaymentioning
confidence: 99%